The Effect Of Implementation Of Shariah Compliance And Islamic Corporate Social Responsibility (ICSR) On Financial Performance With Earning Quality As An Intervening Variable - Lubis, Siti Nurhalizah; Siregar, Saparuddin; Nurlaila (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of Shariah Compliance and Islamic Corporate Social Responsibility (ICSR) implementation on financial performance with earnings quality as an intervening variable in Islamic Commercial Banks in Indonesia for the period 2019–2023. This study uses a quantitative approach with path analysis to examine the direct and indirect relationships between variables. The results show that Shariah Compliance has a significant negative effect on financial performance and earnings quality, while ICSR has no significant effect on financial performance but a significant positive effect on earnings quality. The earnings quality variable is proven to have a significant positive effect on financial performance. The mediation test shows that financial performance is unable to positively mediate the relationship between Shariah Compliance and ICSR on earnings quality. This finding indicates that the implementation of sharia compliance and Islamic-based social responsibility programs still incurs short-term costs, resulting in suboptimal financial impacts, although in the long term it is expected to increase business legitimacy and sustainability. This study contributes to the literature on sharia governance by providing empirical evidence on the role of earnings quality as an intervening variable in the relationship between Shariah Compliance, ICSR, and financial performance in Islamic banks in Indonesia